The 44th SISFA Congress in Arcetri - Gasperini, Antonella; Straulino, Samuele (Il Colle di Galileo, 2025)
From September 17 to 20, 2024, the annual Congress of the Italian Society of Historians of Physics and Astronomy (SISFA) was held at the Department of Physics and Astronomy of the University of Florence and the INAF-Arcetri Astrophysical Observatory. The Congress was an excellent example of the cultural activities that the “Colle di Galileo” memorandum of understanding (signed by CNR, INAF, INFN, and UNIFI) aims to promote and enhance.